PERTANGGUNGJAWABAN PIDANA KORPORASI DALAM TINDAK PIDANA LINGKUNGAN HIDUP BERKAITAN DENGAN DUMPING LIMBAH TANPA IZIN PADA PERUSAHAAN TAMBANG PT. INDOMINCO MANDIRI DI KALIMANTAN - Hesti Lestari; Megawati Barthos (Constitutum: Jurnal Ilmiah Hukum, 2022)
The criminal liability of corporations in environmental crimes, especially regarding crimes related to dumping waste without a permit and not managing B3 waste is regulated in Articles 103 and 104, while the corporation is described in Article 116 paragraph (1) letter a of Law Number 32 Year 2009. PT. Indominco Mandiri is a mining company located in East Kalimantan. In this study, the author uses a normative juridical research method, which discusses corporate criminal responsibility in environmental crimes using the whole theory of criminal responsibility against corporations, namely the theory of strict liability, vicarious liability, the doctrine of delegation, identification, and corporate organs.